THE RELATIONSHIP BETWEEN FINANCIAL LEVERAGE AND FIRM PROFITABILITY: EVIDENCE FROM A SPECIFIC INDUSTRY - Shi Yang; Lei Liang; Li Wen; Yang Junling; Dong Jianchao; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2023)
This study examines the relationship between financial leverage and firm profitability in a specific industry, focusing on the costing systems employed by IHH Healthcare. The research investigates the impact of traditional costing systems, activity-based costing, cost drivers, and cost allocation on financial leverage. The findings reveal that while conventional costing systems do not show a significant relationship with financial leverage, activity-based costing, cost drivers, and cost allocation demonstrate notable connections. The study also highlights the negative effect of leverage on profitability, as excessive debt decreases profitability, particularly in less profitable situations. The research suggests that maintaining an appropriate balance between debt and equity is crucial for optimising company performance. Moreover, the study identifies the challenges faced by IHH Healthcare in managing financial leverage, as the current costing system hampers decision-making in its network of medical centres and hospitals. The research employs a positivist research paradigm and utilises SPSS for accurate measurement and analysis. However, it acknowledges limitations, such as the small sample size and the need for more precise variables in future research within this context.